The Impact of the Capital Structure on the Financial Default / an Analytical Research in Sample of Companies of the Ministry of Industry and Minerals - Saad Sabri, Zahraa; Ismail Abdul Latif , Walaa (Journal of Economics and Administrative Sciences, 2024)
The objective of this research is to study the effect of capital structure on financial default. As it is the first research of its kind that deals with this sample of companies affiliated to the Ministry of Industry and Minerals and these companies were chosen especially because they suffer from financial deficit problems. The importance of this research lies in determining the importance of the components of the capital structure and knowing their impact on financial default in the research sample companies. The research sample represented a number of companies of the Ministry of Industry and Minerals located in Baghdad Governorate. The statistical methods represented in used financial ratios in the analysis to evaluate the research variables, which are both capital structure ratios (Long-term debt ratio to equity and long-term debt to total asset) and liquidity ratios (Current ratio, Quick ratio, Cash ratio) and used the programs (SPSS v26) and (Excel 2010) and the moment structure analysis program (AMOS) was adopted in order to calculate each of the standard deviation, correlation coefficient and specificity to find the relationship between the research variables and test its hypotheses. The results showed that the capital structure had no effect on the cases of financial defaults in the companies.